The efficacy of immune checkpoint blockade for melanoma in-transit with or without nodal metastases – A multicenter cohort study. (July 2022) - Holmberg, Carl-Jacob; Ny, Lars; Hieken, Tina J.; Block, Matthew S.; Carr, Michael J.; Sondak, Vernon K.; Örtenwall, Christoffer; Katsarelias, Dimitrios; Dimitriou, Florentia; Menzies, Alexander M.; Saw, Robyn PM.; Rogiers, Aljosja; et al.
Abstract: Purpose: Guidelines addressing melanoma in-transit metastasis (ITM) recommend immune checkpoint inhibitors (ICI) as a first-line treatment option, despite the fact that there are no efficacy data available from prospective trials for exclusively ITM disease. The study aims to analyze the outcome of patients with ITM treated with ICI based on data from a large cohort of patients treated at international referral clinics. Methods: A multicenter retrospective cohort study of patients treated between January 2015 and December 2020 from Australia, Europe, and the USA, evaluating treatment with ICI for ITM with or without nodal involvement (AJCC8 N1c, N2c, and N3c) and without distant disease (M0). Treatment was with PD-1 inhibitor (nivolumab or pembrolizumab) and/or CTLA-4 inhibitor (ipilimumab). The response was evaluated according to the RECIST criteria modified for cutaneous lesions. Results: A total of 287 patients from 21 institutions in eight countries were included. Immunotherapy was first-line treatment in 64 (22%) patients. PD-1 or CTLA-4 inhibitor monotherapy was given in 233 (81%) and 23 (8%) patients, respectively, while 31 (11%) received both in combination. The overall response rate was 56%, complete response (CR) rate was 36%, and progressive disease (PD) rate was 32%. Median PFS was ten months (95% CI 7.4–12.6 months) with a one-, two-, and five-year PFS rate of 48%, 33%, and 18%, respectively. Median MSS was not reached, and the one-, two-, and five-year MSS rates were 95%, 83%, and 71%, respectively. Conclusion: Systemic immunotherapy is an effective treatment for melanoma ITM. Future studies should evaluate the role of systemic immunotherapy in the context of multimodality therapy, including locoregional treatments such as surgery, intralesional therapy, and regional therapies. Highlights: The efficacy of immunotherapy for melanoma in-transit metastases is unknown. An international multicenter retrospective cohort study. Systemic immunotherapy is an effective treatment for melanoma in-transit metastases.